Respostas
respondido por:
3
Método da Adição:
m + 3n = - 1
m + 4n = 1
----
5
5m + 20n = 1
------------ -----
5 5
5m + 20n = 1
m + 3n = - 1 (-5)
5m + 20n = 1
- 5m - 15n = 5 (+)
-----------------------------
5n = 6
n = 6
-----
5
m + 3n = - 1
m + 3. 6 = - 1
------
5
5m + 18 = - 5
----------- -----
5 5
5m + 18 = - 5
5m = - 5 - 18
5m = - 23
m = - 23
-------
5
m + 3n = - 1
m + 4n = 1
----
5
5m + 20n = 1
------------ -----
5 5
5m + 20n = 1
m + 3n = - 1 (-5)
5m + 20n = 1
- 5m - 15n = 5 (+)
-----------------------------
5n = 6
n = 6
-----
5
m + 3n = - 1
m + 3. 6 = - 1
------
5
5m + 18 = - 5
----------- -----
5 5
5m + 18 = - 5
5m = - 5 - 18
5m = - 23
m = - 23
-------
5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás